Absorption of iron from grape-molasses and ferrous sulfate: a comparative study in normal subjects and subjects with iron deficiency anemia - Aslan, Yakup; Erduran, Erol; Mocan, Hilal; Gedik, Yusuf; Ökten, Ayşenur; Soylu, Hanifi; Değer, Orhan (The Turkish Journal of Pediatrics, 1997)
We compared the absorption of iron from grape molasses (GM) and ferrous sulfate (FS) using the post-absorptive serum iron increase method (non-radioactive). The study involved 56 subjects, aged 6-36 months. Group I consisted of 30 subjects with iron deficiency anemia (IDA) and group II, 26 non-anemic subjects. Each group was subdivided randomly into two equal subgroups to be given either GM or FS. The absorption of the iron from GM was monitored in 15 infants with IDA and in 13 non-anemic infants, and the absorption of iron from FS was tested in the rest of the subjects in each group.In those infants in each group given GM or FS, there was no significant difference in before-test values for serum iron (SI) and total iron binding capacity (TIBC) (p > 0.05). In the group with IDA, the mean after-test SI value in FS-given infants was higher and the mean TIBC value lower than those of GM-given infants (p < 0.05). However, in the non-anemic group, there was no significant difference in the mean after-test SI and TIBC values in either GM- or FS-given infants (p > 0.05).The mean increase of serum iron in GM-given infants with IDA was 27.0 ± 13.4 µg/dl and in FS-given infants, 60.6 ± 17.0 µg/dl (p < 0.05). In the non-anemic group, the mean increase of serum iron of GM-given infants was 23.0 ± 4.3 µg/dl, and that of FS-given infants, 23.8 ± 10.0 µg/dl (p > 0.05).We determined that in non-anemic subjects, the absorption of iron from GM was comparable to that from FS. Furthermore, we believe that grape molasses is an effective iron source in preventing iron deficiency anemia in infancy.
Keywords: iron absorption; grape molasses; ferrous sulfate